Hubungan Minat Belajar dengan Hasil Belajar Penataan Rambut pada Siswa SMP 138 Terbuka Cakung 3 Jakarta - Ewa Sundari; Mari Okatini Armandari; Neneng Siti Silfi (Mathematics Education Study Program, 2025)
The research made with purpose to get the data of interest in learning and get the data about the result study hair styling also to know there or not the positive relation Between interest in learning and hair styling learning outcomes among students at SMP 138 Open Cakung 3 Jakarta. This research use approach correlasional. The population of this study were all life skills students at SMP 138 Open Cakung 3 Jakarta. Taking sample method in this research is purposive sampling. The sample criteria in this study were students who were taking life skills hair styling lessons at SMP 138 Open Cakung 3 Jakarta. So, the sample in this study was 32 class VIII students who took life skill. The data analysis technique used is associative quantitative techniques, analysis requirements tests, data normality tests, linearity tests. The result of this research swown that there are positive relation and significant between interest in learning and hair styling learning outcomes for students at SMP 138 Open Cakung 3 Jakarta. The majority of learning outcomes for students are in the medium category, namely 65.6%. And according to the research results, it shows that the majority of students' interest in learning is in the medium category at 78.1%. There fore, the higher the interest in learning, the higher the hair styling learning outcomes achieved by students.